Is There Time Enough? Temporal Resources and Service Performance in the Danish Home Care Sector - Tufte, Pernille (Nordic Journal of Working Life Studies, 2013)
Reflecting on the temporal conditions of home care work, care workers are fairly critical, stressing that time frames are inflexible and time is limited and occasionally insufficient, altogether constituting a time pressure in work performance. Besides from the immediate consequences of time scarcity in the daily work performance, care workers relate the issue of time to a more fundamental discussion of what the performance of care does and should entail. The purpose of the article is to examine care workers’ perceptions of the temporal conditions of care work, investigating how time pressure constitutes a challenge to care workers’ own sense and valuation of their work. The article is informed by two theoretical perspectives: standardization of care services and performance of care work in private homes. Empirically, the article examines how care workers perceive the relations between the temporal framing and the possibilities to perform care work. Methodologically, the article is based on qualitative data, collected through focus group interviews and participant observation, and analyzed within the perspective of reflexive interpretation, using grounded theory method and hermeneutic approaches of analysis. A central focus of analysis is the concept of “additional care services.” The use of the concept reflects different understandings of care. Relying on the logic of standardization, managers articulate additional services as definite items, which could (and should) be left out of the performance of care work. Care workers do, however, not accept this notion. Relying on their experience of work, they perceive additional services as an ambiguous concept, which recognizes the multiple character of care work. Conclusions are that time scarcity constitutes a pressure on work performance as a whole, reducing care workers’ flexibility, challenging their authority, but still keeping them in a position of responsibility. Ultimately, the battle on time reflects the ambivalences in care work—ambivalences that are becoming increasingly difficult for care workers to handle in work performance.